Women's Personality in The Qur'an (Contextualizing QS. Al-Tahrim:10-12 Through the Approach of Ma'na Cum-Maghza): Kepribadian Perempuan dalam Al-Qur'an (Kontekstualisasi QS. Al-Tahrim: 10-12 melalui Pendekatan Cum Ma'na Cum Maghza ) - An-Nur, Vina Umdatun Najakhah; Riyadi, Abdul Kadir; Nabilah, Is’ad Durrotun (Ulumul Qur'an: Jurnal Kajian Ilmu Al-Qur'an dan Tafsir, 2025)
This article contains interpretations of women's personality based on the Qur'an and relevant with this modern era from contextualization Mana Cum Maghza hermeneutics method. Today, womens personality so different from the old's era. Women in olds era had simple characteristics became modern women which some person be ruled out from syariat. The author was interested to take from several verses of the Qur'an in this research, QS. At-Tahrim 10-12. From the limits of the verses focused with the interpretations: Firstly, its emphasized that women should protect their modesty by averting gaze and covering private parts, except their mahram. Secondly, women are encouraged to maintain a sense of modesty and reserve in their interactions with men. Thirdly, they are urged not to engage in behaviors that may be interpreted as flirtatious. Lastly, reminded importance of remaining faithful and loyal to their spouses. Conclusion in this research that women can wear clothes with trending fashion and conditions with boundaries also give more space when interacting with men except their mahram. As far as, follow the trend of fashion still according based on syariat and principles of covering their modesty and comply with religious guidance.